HOW VALUABLE WAS MUSIC FOR CLOISTERED NUNS? A CASE STUDY IN SÃO BENTO DE CÁSTRIS (ÉVORA, PORTUGAL) 92 - Elisa Lessa; Margarida Sá Nogueira Lalanda (European Scientific Journal, ESJ, 2015)
In the past, living together within a community was a form of isolating oneself from the world as well as a means to perfect oneself through the observance of several moral precepts. Generally speaking, what defined life within a convent, besides the reclusion from society and the solitary life that it entailed, was a very strict spiritual program that included not only prayer, but also attending to the Divine Offices. A careful reading of the expense books prepared by the treasurer nuns reveals the costs spent on musical practice, as well as other expenses with which it is compared in this article. This study, carried out by analyzing costs relating to Music in Benedictine and Clare monasteries and, in particular, in the Cistercian Monastery of St. Benedict of Cástris (Évora, Portugal) in the post Trento period, shows that a significant part of the monasteries budget was devoted to expenses with guest musicians, musical instruments, choir books, special food and "gifts" for the musician nuns as a recognition for their music.